Isolasi Biflavonoid Baru dari Garcinia tetranda Pierre Berdasarkan Jalur Biogenesis dan Aktivitas terhadap Antibakteri - Sulistyaningrum, Novi; Ersam, Taslim (Jurnal Kefarmasian Indonesia, 2012)
Garcinia tetranda Pierre (Clusiaceae) is a plant that is widely used to treat various diseases and its chemical compounds has not been much studied. Compound isolation using the three methods of chromatography (Vacuum Liquid Chromatography Column (VLCC), preparative Thin Layer Chromatography (pTLC) and TLC) generate novel compound 5,7,4 ', 5'', 7'', 3''', 4 '''-heptahidroksi-2'''-methoxy-flavanon [ 3,8 ]-flavone'' which is different from the compounds that had been found previously in Garcinia tetranda Pierre. Structure identification was conducted using UV, IR and NMR spectroscopic data and by comparing the 13C and 1H-NMR data of the isolate compound and known biflavonoid compounds. Biogenesis pathway analysis of the new compound showing relationship with molecular compounds which have previously been found in Garcinia. Antibacterial test of the novel compound using Kirby-Bauer agar diffusion methode against Gram-negative bacteria Salmonella typhi showed that the compound is not potentially used as antibacterial agent compared to chloramphenicol.